Statins in Peripheral Arterial Disease - Chiesa, Scott T.; Papageorgiou, Nikos; Charakida, Marietta (Current Pharmaceutical Design, 2017)
Peripheral arterial disease (PAD) is a common atherosclertico condition affecting the lower extremities. PAD patients share similar cardiovascular risk factors to coronary artery disease patients and suffer from increased cardiovascular morbidity and mortality. Statins have been widely used in coronary artery disease patients but have been underused in patients with PAD. In the current review, we present data which support the beneficial role of statins in both reducing cardiovascular events and improving symptom-related outcomes in PAD patients. Alongside their lipid lowering effects, their pleiotropic actions are also discussed. Recent guidelines, which strongly recommend the administration of statins in PAD patients, are also presented.
Keywords: outcomes